Population genetics of the Mediterranean fruit fly Ceratitis capitata in the Western Cape Province, South Africa : invasion potential and dispersal ability - Karsten, Minette (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.